Profil Perikanan Tangkap Di Danau Barito Mati Desa Penda Asam Kecamatan Dusun Selatan Kabupaten Barito Selatan - Sweking, Sweking; Aunurafik, Aunurafik; Najamuddin, Anang; Firlianty, Firlianty (Universitas Lambung Mangkurat, 2019)
This study aims to determine the description/profile of catch fisheries in lake Barito Mati from economic aspects, aspects of fishing and social community fisherman. This study was conducted for 2 weeks in the field to collect primary data and secondary data. The method used is the method of observation or direct observation with interview techniques using questionnaire (questionnaire), Respondents with the main job as a fisherman. Respondents as many as 19 (nineteen) people with experience as fisherman 4 years – 30 years. Capture fisheries profile in lake Barito Mati from the economic aspect, catch aspect and social aspect of society are summed up in good condition and deserve to be cultivated as the source of income with average profit Rp. 5.171.794,-/month above the value of Regional Minimum Wage (UMR) South Barito Regency Of 2017 of Rp. 2.546.000/ month.